Managing higher education graduate enrollment - Tilakov Sherzod Akbarovich (THE INNOVATION ECONOMY, 2026)
This article examines the theoretical and practical aspects of managing the level of graduates’ access to higher education. The study analyzes ways to improve the efficiency of admission processes, identifies key factors influencing enrollment coverage, and explores mechanisms for enhancing management practices in the higher education system. The interaction between government policy, regional capacities, competitive environment, and labor market demands in attracting graduates to higher education is also investigated. The article concludes with practical recommendations and strategic directions aimed at increasing the overall coverage of graduates in higher education